About the impact of model risk on capital reserves: A quantitative analysis - Philip Bertram; Philipp Sibbertsen; Gerhard Stahl (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
This paper analyzes and quantifies the idea of model risk in the environment of internal model building. We define various types of model risk including estimation risk, model risk in distribution and model risk in functional form. By the quantification of these concepts we analyze the impact of the modeling process of an econometric model on the resulting company model. Utilizing real insurance data we specify, estimate and simulate various linear and nonlinear time series models for the inflation rate and examine its impact on pension liabilities under the aspect of model risk. Under consideration of different risk measures it is shown that model risk can differ profoundly due to the specification process of the econometric model resulting in remarkable monetary differences concerning capital reserves. We furthermore propose a specification strategy for univariate time series models and demonstrate that thereby market risk and capital reserves can be reduced distinctively.
Keywords: G12; G18; 330; Model risk; estimation risk; misspecification risk; Basel multiplication factor; empirical model specification; capital reserves; Ökonometrisches Modell; Risiko; Statistischer Fehler; Zeitreihenanalyse; Versicherungstechnisches Risiko; Basler Akkord; Theorie